Особливості ортопедичного лікування дефектів зубних рядів у дітей з особливими потребами в період тимчасового прикусу - Гавриленко, Марина Аркадіївна; Gavrilenko, M. A. (My University, 2014)
На протязі 5 років було досліджено використання часткових знімних протезів у дітей з особливими пот-ребами при лікуванні дефектів зубних рядів в період тимчасового прикусу. Виявлено ефективність викорис-тання загального знеболення при протезуванні знімними протезами. Summary. The use of partial removable dentures in disabled children in the treatment of dentition defects in the period of temporary occlusion was studied during 5 years. The efficiency of general anesthesia in prosthetics using re-movable dentures as a method of prevention of dentition pathology in disabled children was revealed. Aim: development of recommendations on the use of general anesthesia in the production of removable dentures in disabled children with the temporary occlusion. Materials and methods of the research. The study involved 60 disabled children aged from 2 to 6 years old, who underwent complex dental treatment under general anesthesia in several stages. For 45 children jaws imprinting under general anesthesia and production of removable dentures were carried out during the second stage of treatment. For 15 children with mental disorders prosthetics was not performed in the presence of contraindications. Observations were carried out from March 2010 to March 2014. Results: in all groups of children high level of premature removals of frontal deciduous teeth and high prevalence of complicated caries were revealed. The most effective method of treatment was two-step comprehensive one using general anesthesia in the first and in the second case. Conclusions: recommendations on providing orthopedic care for disabled children between the ages of 2 and 6 years old with partial adentia were developed. The first stage is sanitation of the oral cavity under general anesthesia. The second stage - jaws imprinting is performed under general anesthesia. General anesthesia gives an opportunity to make high-quality removable dentures, children get used to them quickly. Thus prevention of dentoalveolar defor-mations is carried out.
The peculiarities of orthopedic treatment of edentulous spaces in children with special demands at milk occlusion
Keywords: діти з особливими потребами; дефект зубного ряду; тимчасові зуби; загальне знеболення; профілактика зубощелепних деформацій; disabled children; the defect of dentition; deciduous teeth; general anesthesia; prevention of dentoalveolar deformations